Acute effect of low-intensity aerobic exercise on eliciting enhanced parietal activation and promoting executive function performance more than moderate-intensity exercise - Lingling, Shen; Huaqing, Chen; Xuan, Li; Jichen, Cai; Chenxi, Li; Chuhuai, Wang (Frontiers in Physiology, 2025)
IntroductionAerobic exercise intensity differentially impacts cognitive function and brain activity, but the optimal intensity for enhancing cognitive function and cortical activity remains unclear. This study investigates the effects of low- and moderate-intensity aerobic exercise (LAE/MAE) on cognition, gait, and brain dynamics in healthy young adults.MethodsForty-nine participants were assigned to stretching (SE), LAE, or MAE groups, and their cognitive function was assessed using various tasks before and after exercise, cortical activation was monitored using functional near-infrared spectroscopy, and gait parameters and stability indices were measured using a video motion and posture analysis system.ResultsThe LAE group exhibited significantly improved Stroop task reaction time and reduced deoxyhemoglobin concentrations in key cortical regions (left/right S1, left Broca’s area, and right dorsolateral prefrontal cortex). Greater stride length during aerobic exercise correlated with the Stroop task reaction time, and functional connectivity indices during exercise predicted post-exercise cognitive benefits. Notably, LAE enhanced functional connectivity within the parietal cortex, fostering interconnections between left M1 and nearby brain regions including left S1, right M1, and Wernicke’s area.DiscussionLAE optimizes parietal functional connectivity and executive speed, with stride length and cortical functional connectivity predicting post-exercise cognitive benefits. These findings advance our understanding of the relationships between exercise and brain health, particularly those linked with motor learning and M1 plasticity-mediated cortical network dynamics.